Pengaruh Kecanduan Game Online Terhadap Keterampilan Sosial Individu: Analisis Dampak dan Implikasi - Angellita Satura; Hastuti Rifayani (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Online gaming has become a global phenomenon that has attracted the attention of many individuals, especially the younger generation. As its popularity continues to increase, issues have also emerged regarding the impact of online gaming addiction, especially in the context of its effect on an individual's social skills. Online game addiction is a serious concern because it can affect an individual's ability to interact with the real world, including the ability to communicate, build interpersonal relationships, and resolve conflicts in everyday life. Therefore, it is necessary to dig deeper into the influence of online game addiction on an individual's social skills. The aim of this research is to determine the impact of online game addiction on individual social skills. The research method used is qualitative research with an open questionnaire as a data collection instrument. The research results show that there is a significant negative influence of addiction to playing online games on individual social skills. That is, the more often individuals play online games, the lower the social skills they have